2016
DOI: 10.1038/srep34307
|View full text |Cite
|
Sign up to set email alerts
|

Soybean GmDREBL Increases Lipid Content in Seeds of Transgenic Arabidopsis

Abstract: A DREB-type transcription factor gene GmDREBL has been characterized for its functions in oil accumulation in seeds. The gene is specifically expressed in soybean seeds. The GmDREBL is localized in nucleus and has transcriptional activation ability. Overexpression of GmDREBL increased the fatty acid content in the seeds of transgenic Arabidopsis plants. GmDREBL can bind to the promoter region of WRI1 to activate its expression. Several other genes in the fatty acid biosynthesis pathway were also enhanced in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 45 publications
0
36
0
Order By: Relevance
“…Y. Q. Zhang et al (2016) reported that levels of GmDREBL, a seed-specific TF, were related to seed lipid content through the expression of GmWRI1-like1, but not by GmWRI1-like2, since GmDREBL was able to bind to the DRE cis-element present in GmWRI1-like1 promoter region regulating its expression. Furthermore, WRI1 is a direct target of FUSCA3 (FUS3) and LEAFY COTYLEDON2 (LEC2) which are master regulators with roles in seed oil biosynthesis (Devic & Roscoe, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Y. Q. Zhang et al (2016) reported that levels of GmDREBL, a seed-specific TF, were related to seed lipid content through the expression of GmWRI1-like1, but not by GmWRI1-like2, since GmDREBL was able to bind to the DRE cis-element present in GmWRI1-like1 promoter region regulating its expression. Furthermore, WRI1 is a direct target of FUSCA3 (FUS3) and LEAFY COTYLEDON2 (LEC2) which are master regulators with roles in seed oil biosynthesis (Devic & Roscoe, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it was found that GmDREBL promotes WRI1 expression and thus oil accumulation in arabidopsis seeds, and soybean plants that overexpressed GmDREBL in hairy roots enhanced the expression of a soybean WRI1 homolog, GmWRI1-like1 (Y. Q. Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…WRI1 is regulated by LEC1, LEC2 and GmDREBL at the transcriptional level. WRI1 is also regulated by 14‐3‐3, KIN10 and perhaps by OST1 at the protein level (Baud et al 2007; Mu et al 2008; Baud et al 2009; Sirichandra et al 2010; Ma et al 2016; Zhang et al 2016; Zhai et al 2017; Kong and Ma 2018). To date, we still have an incomplete understanding of the roles of ABA in regulating seed storage‐related proteins and genes.…”
Section: Abscisic Acid In Seed Developmentmentioning
confidence: 99%
“…Our study indicates dual roles for soybean HSFB2b in both salt stress response and seed trait regulation. A similar phenomenon has been observed for soybean GmDREBL, which can increase seed oil accumulation and improve stress tolerance in plants (Y. Q. Zhang et al ., ). The fact that the same gene has roles in both stress responses and seed trait regulation suggests that plants may utilize these genes in an efficient manner.…”
Section: Discussionmentioning
confidence: 97%